Lessons learned from a lung cancer screening patient navigation program at a safety-net hospital system. Issue 28 (1st October 2022) - Semlow, Andrea R; Natchimuthu, Vijaya Subbu; Lee, Simon Craddock; Gerber, David E; Zhu, Hong; Hamann, Heidi A.; Browning, Travis; Santini, Noel O.; Lee, Jessica L.
Abstract : 121 Background: As part of a CPRIT prevention services grant led by UTSW, Parkland Health adapted a patient navigation model previously piloted in 2017 to optimize low-dose computed tomography (LDCT) imaging for lung cancer screening and evidence-based tobacco cessation services. Methods: Non-clinical patient navigators (PN) contacted patients with a LDCT order to discuss their lung scan and smoking cessation options via telephone encounters. The PN has three planned touchpoints to assess patient knowledge, identify barriers, and refer to appropriate resources. Program evaluation data has been collected monthly for enrolled patients (n = 460) from August 2021-June 2022 via REDCap and EPIC. Navigation excluded patients who were incarcerated, had no phone number listed in medical record, or patients opted out of the program on intake. Results: Of the LDCT-eligible patients, PNs were able to complete two or more navigation calls with 55.62% of patients assigned. 77% of patients completed their first LDCT, compared to 80% in the initial trial. The most common barriers to screening completion included transportation (n = 38), insurance coverage (n = 22), and cost (n = 9). Of the navigated patients who were active smokers (75%), 33% scheduled at least one smoking cessation-related visit. Some patients unresponsive to conversations about quitting, were responsive to language around "reducing" tobacco use. Conclusions: Disproportionately under- and uninsured, Parkland Health patients face a variety of barriers to screening. As a result, PN staff must balance reaching all patients with a LDCT order and spending additional time navigating patients with complex barriers. To address these barriers, the PN program facilitates coordination of patients between primary care providers, radiology operations, smoking cessation clinics, patient financial services, lung diagnostic clinic, and social work. For example, patients can schedule a smoking cessation visit directly with our PN instead of being referred. As Parkland has a decentralized LCS program model, having embedded non-clinical PNs within existing roles in the cancer center, like medical practice assistants, increases continuity of care. These individuals have the benefit from day-to-day knowledge of downstream services that bolster their ability to connect patients to external services to address barriers.